Pengelolaan Administrasi Birokrasi Pada Masa Sultan Mahmud Badaruddin II Di Kesultanan Palembang Darussalam Pada Tahun 1803-1821 - sari febriani (INC- Islam Nusantara Center, 2022)
Administrasi adalah perencanaan, pengendalian, dan pengorganisasian pekerjaan pemerintahan, serta pergerakan mereka yang melaksanakannya agar mencapai tujuan yang telah ditetapkan. Sedangkan birokrasi menunjuk pada suatu organisasi yang dimaksudkan untuk mengerahkan tenaga dengan teratur dan terus-menerus, untuk mencapai suatu tujuan tertentu. Pengelolaan administrasi birokrasi pada masa Kesultanan Mahmud Badaruddin II bertujuan untuk mengetahui riwayat hidup Sultan Mahmud Badaruddin II, menguraikan sejarah Kesultanan Palembang Darussalam serta menjabarkan pengelolaan administrasi birokrasi pada masa Sultan Mahmud Badaruddin II di Kesultanan Palembang Darussalam. Administration is planning, controlling, and organizing the work of government, and the movement of those who implement it in order to achieve the goals that have been set. While bureaucracy refers to an organization that is intended to exert energy regularly and continuously, to achieve a certain goal. Management of bureaucratic administration during the Mahmud Badaruddin Sultanate II aims to know the history of Sultan Mahmud Badaruddin II, describes the history of the Sultanate of Palembang Darussalam and describes the management of bureaucratic administration in the time of Sultan Mahmud Badaruddin II in Palembang Darussalam Sultanate. This thesis uses primary data source and secondary data source. The primary source is a book written by P. DE ROO DE FAILLE entitled From The Age of Palembang Sultanate, translated by Soegarda Poerbakawatja. The secondary sources include the form of books, journals and others. All sources of data are collected by historical methods of heuristics and verification in which researchers review documents are generally focused on documents recording experts from various fields and other sources containing information about the past or that is worthy of historical value. Heuristics and verification serves to select historical data that the facts (evidence) history has been valid and that has been tested the validity and reliability, then the process of historiography. In addition, researchers also collect qualitative data consisting of observation and documentation. Technique of data analysis in this research is qualitative descriptive based on logic of science. In a study entitled